Image and global resemblance in the light of hadith “Who so imitates other people becomes one of them” - Demirel, Serdar (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
In today’s world, people from different countries, cities and institutions unprecedentedly resemble each other in every aspect of life. Likewise, the deeds and imagery aspirations of Oriental and Occidental people also resemble. In such an atmosphere, the local cultures rooted in history become accessories and lose their historical significance and metaphysical aspects in the edifice of the society. This study aims to analyze Prophet Muhammad’s (s.a.w.) warning, “Who so imitates other people becomes one of them”, its layers of meaning and its relationship with “image and global resemblence”.